2009
DOI: 10.1086/598856
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection ofPlasmodium falciparumDNA in Saliva, Blood, and Urine

Abstract: Saliva sampling is a promising less-invasive approach for detecting malaria infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
108
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 32 publications
9
108
1
Order By: Relevance
“…The present observation supports the limited reports describing potential to diagnose malaria using saliva samples. [8][9][10] The high sensitivity (detection threshold > 2,000 parasites/ μL of blood) and specificity of the Optimal-IT dipsticks in patient blood at presentation as observed in this study are consistent with previous reports. [14][15][16] Results from the present study show that spinning saliva samples before analysis significantly decreased the sensitivity for antigen detection by the RDT (sensitivity = 48.3%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present observation supports the limited reports describing potential to diagnose malaria using saliva samples. [8][9][10] The high sensitivity (detection threshold > 2,000 parasites/ μL of blood) and specificity of the Optimal-IT dipsticks in patient blood at presentation as observed in this study are consistent with previous reports. [14][15][16] Results from the present study show that spinning saliva samples before analysis significantly decreased the sensitivity for antigen detection by the RDT (sensitivity = 48.3%).…”
Section: Discussionsupporting
confidence: 90%
“…In a recently reported study using quantitative PCR analysis, it was shown that the amount of parasite DNA quantified in peripheral blood samples from infected patients was ~600-fold greater than in saliva samples, although a statistically significant correlation between parasite density and amount of parasite DNA in saliva was observed. 9 A full understanding of biological processes leading to the release of parasite antigen in saliva would provide more insight into these disparities. Furthermore, matched blood and saliva RDTs of four patients with microscopically confirmed P. falciparum malaria were negative despite high parasite densities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent discovery that Plasmodium can be genotyped from urine or saliva in humans (6,7) and that fecal primate samples have allowed researchers to identify the ancestors of the HIV-1 epidemic in chimpanzees and gorillas (8,9) moved us to explore whether similar noninvasive approaches could be used to investigate the diversity of malaria parasites in wild populations of apes (chimpanzees and gorillas) in Africa. This is, indeed, the case.…”
mentioning
confidence: 99%
“…The recent discovery that Plasmodium can be genotyped from urine, saliva, and fecal primate samples (5,27,28) has opened up considerably the opportunities to explore the presence of Plasmodium in apes, as well as in other primates and in all other sorts of animals, by noninvasive methods. Prugnolle et al (29) have analyzed partial Cytb sequences (704 nucleotides) from five chimpanzee and seven gorilla DNA samples, obtained from fecal samples from wild chimpanzees (n = 125) and gorillas (n = 84) from Cameroon, plus three blood samples from captive wild-born gorillas from Gabon.…”
mentioning
confidence: 99%